Maintenance Costs Optimization Of Light Rail Transit (LRT) Facilities And Infrastructure Based On Life Cycle Cost Analysis (Case Study: South Sumatra LRT) - Atri Ranindita; Ayomi Dita Rarasati (Eduvest - Journal of Universal Studies, 2024)
The construction of the South Sumatra Light Rail Transit (LRT) requires a huge development cost, besides that it has quite a large annual operational and maintenance cost. In order for South Sumatra LRT maintenance costs to run efficiently and effectively, it is necessary to optimize maintenance costs for South Sumatra LRT facilities and infrastructure based on Life Cycle Cost Analysis. Life Cycle Cost is an economic analysis method that refers to all costs associated with development, operating and maintaining a construction project over a certain period of time (Heralova, 2017). The research objectives were to analyze the physical condition of Facilities and Infrastructure South Sumatra LRT, evaluate South Sumatra LRT maintenance strategies and develop maintenance cost scenarios based on Life Cycle Cost. Based on data processing using the combined condition index method, the total value of the South Sumatra LRT infrastructure components reached 5,718. The physical condition of the South Sumatra LRT infrastructure reviewed is on a good scale with minor damage so that the option of preventive or time-based maintenance activities can be used. For the Life Cycle Cost of South Sumatra LRT infrastructure, the value obtained is IDR 2,080,482,508,541,480.